Handbook of computational approaches to counterterrorism - Subrahmanian, V. S. (Springer, 2013)
The last 20 years have witnessed an unprecedented change in information and communications technologies, leading to the ability not only to disseminate information in seconds from one part of the world to another, but also the ability to organize, analyze, understand and predict phenomena on the basis of that information. This book studies how computational methods can substantially improve the collection of data about terrorist groups, the analysis of that data through the construction of behavioral models, the ability to forecast what such groups might do, and how one might respond to a groupu2019s behavior.